Arbitrage-free Nelson–Siegel model for multiple yield curves - Riccardo Brignone; Christoph Gerhart; Eva Lütkebohmert (Mathematics and Financial Economics, 2021)
We propose an affine term structure model that allows for tenor-dependence of yield curves and thus for different risk categories in interbank rates, an important feature of post-crisis interest rate markets. The model has a Nelson–Siegel factor loading structure and thus economically well interpretable parameters. We show that the model is tractable in terms of estimation and provides good in-sample fit and out-of-sample forecasting performance. The proposed model is arbitrage-free across maturities and tenors, and thus perfectly suited for risk management and pricing purposes. We apply our framework to the pricing of caplets in order to illustrate its practical applicability and its suitability for stress testing.
Keywords: E43; G12; G17; 330; Affine processes; Dynamic factor model; Multiple term structures; Nelson–Siegel curve